(untitled) (Homoeopathy for All, 2023)
In the absence of congenital urinary tract malformations or congenital or acquired central nervous system problems, nocturnal enuresis is defined as intermittent incontinence during sleep in a child aged 5 years or older. [1] Enuresis is generally distressing for both children and parents, and it has a negative impact on family life in many circumstances. Self-esteem issues, social isolation, low academic achievement, and psychological issues are all common.[1]